2018
DOI: 10.1002/cphc.201800506
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous ZnFe2O4 Photoanodes with Template‐Tailored Mesopores and Temperature‐Dependent Photocurrents

Abstract: Mesoporous ZnFe O photoanodes have been prepared via dip-coating utilizing the evaporation-induced self-assembly of two different block-copolymer templates to investigate the influence of pore geometry on the photoelectrochemcial performance of those earth-abundant photoelectrodes. The use of commercial block copolymers, triblock copolymer Pluronic F127 and the diblock copolymer PIB3000 as templates, leads to different pore morphologies under identical preparation conditions due to different polymer stabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 40 publications
6
42
0
Order By: Relevance
“…When not employed as single‐phase electrodes, spinel ferrites are also often used in the form of composites as a kind of sensitizer for better charge separation, e. g. in combinations like ZnFe 2 O 4 /α‐Fe 2 O 3 or NiFe 2 O 4 /TiO 2 . Recently, it has been shown that the photoelectrochemical properties of ZnFe 2 O 4 can be tailored by mesostructural engineering . To this end, large‐pore mesoporous ZnFe 2 O 4 thin films, prepared using an evaporation‐induced self‐assembly (EISA) process along with different polymer structure‐directing agents, were applied.…”
Section: Figurementioning
confidence: 99%
“…When not employed as single‐phase electrodes, spinel ferrites are also often used in the form of composites as a kind of sensitizer for better charge separation, e. g. in combinations like ZnFe 2 O 4 /α‐Fe 2 O 3 or NiFe 2 O 4 /TiO 2 . Recently, it has been shown that the photoelectrochemical properties of ZnFe 2 O 4 can be tailored by mesostructural engineering . To this end, large‐pore mesoporous ZnFe 2 O 4 thin films, prepared using an evaporation‐induced self‐assembly (EISA) process along with different polymer structure‐directing agents, were applied.…”
Section: Figurementioning
confidence: 99%
“…Among the multiple transition metal oxides, ferrites with the general formula M II Fe 2 O 4 (M=Ca, Zn, Mg, Ni, Co, Mn etc .) have gained considerable attention due to their compositions made up from earth‐abundant elements and widespread application fields besides electrocatalysis [12–15] in gas sensing, [16,17] and photocatalysis/photoelectrochemistry [18–27] . Especially nickel ferrite has been considered as efficient OER electrocatalyst, with outstanding high stability in alkaline media, excellent redox properties, and ferromagnetism facilitating the catalyst separation from solution [28,29] .…”
Section: Introductionmentioning
confidence: 99%
“…have gained considerable attention due to their compositions made up from earth-abundant elements and widespread application fields besides electrocatalysis [12][13][14][15] in gas sensing, [16,17] and photocatalysis/photoelectrochemistry. [18][19][20][21][22][23][24][25][26][27] Especially nickel ferrite has been considered as efficient OER electrocatalyst, with outstanding high stability in alkaline media, excellent redox properties, and ferromagnetism facilitating the catalyst separation from solution. [28,29] Already in 1999, N. K. Singh and R. N. Singh showed that the inverse spinel NiFe 2 O 4 is a highly active material in the electrocatalytic water oxidation with an overpotential of 379 mV at a current density of 100 mA cm À 2 , which outcompetes pure iron oxide (spinel Fe 3 O 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the last few years, there has been increasing interest in the study of spinel ZnFe 2 O 4 (ZFO) as a photoanode material for photoelectrochemical water oxidation [1][2][3]. As new scientific investigations in this field are reported, differences concerning the photoelectrochemical activity of ZFO photoanodes prepared by different routes have become evident [4][5][6][7][8][9][10][11]. It is well known that ZFO exhibits a variable structure where the distribution of Zn 2+ and Fe 3+ cations between octahedral and tetrahedral sites within the crystal lattice depends on the synthetic conditions [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%